2005
DOI: 10.1002/jctb.1391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of naphthalene biodegradation efficiency of Pseudomonas and Burkholderia strains tested in soil model systems

Abstract: The kinetic parameters of the naphthalene degradation process performed by indigenous and introduced microorganisms were studied in soil model systems. The introduction of active naphthalenedegrading strains Pseudomonas putida BS3701 and G7 in soil model systems accelerated the naphthalene destruction process by a factor of three to four. Moreover, the addition of salicylate (0.1 mg g −1 dry soil) to the systems containing the introduced microbial strains again doubled the rate of the naphthalene degradation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…and Burkholderia sp. are gram negative soil bacteria and have been previously documented as excellent degraders of a wide range of xenobiotics and recalcitrant compounds both in soil and water environment (Radehaus and Schmidt 1992;Filonov et al 2006). These efficient bacterial strains degraded both isomers of endosulfan i.e., a-and b-endosulfan more than 90% within 14 days of incubation.…”
Section: Discussionmentioning
confidence: 97%
“…and Burkholderia sp. are gram negative soil bacteria and have been previously documented as excellent degraders of a wide range of xenobiotics and recalcitrant compounds both in soil and water environment (Radehaus and Schmidt 1992;Filonov et al 2006). These efficient bacterial strains degraded both isomers of endosulfan i.e., a-and b-endosulfan more than 90% within 14 days of incubation.…”
Section: Discussionmentioning
confidence: 97%
“…Costerton and Lappin-Scott [36] had stated that the planktonic single species laboratory culture exerts a powerful selective pressure on a bacterial genome that eventually produces a cell that lacks protective and adhesive surface structures that cannot survive in natural environments where adhesion and protection is of paramount importance. Filonov et al [18,37] showed naphthalene degradation for the concentration of 1 mg/g and 2.5 mg/g in soil model systems in 8 days and 3 days respectively. Pseudomonas sp.…”
Section: Microcosm Studies To Examine the Potential Of Pseudomonas Spmentioning
confidence: 98%
“…Bioremediation is thought a feasible and economical way to remove petroleum pollutants from contaminated soil or water (Alexander, 1999;Head and Swannell, 1999;Rittmann and McCarty, 2001;Piskonen et al, 2005;Filonov et al, 2006;Mihial et al, 2006;Gallego et al, 2007;Lin et al, 2010). However, mineralization of complex hydrocarbon mixtures such as those comprising diesel fuels usually requires the coexistence and effective mutualism of several specialized microorganisms with complementary substrate specificity (Rambeloarisoa et al, 1984;Alexander, 1999;Richard and Vogel, 1999).…”
Section: Introductionmentioning
confidence: 98%